2010
DOI: 10.1177/1049909110382770
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Favorable Attitudes Toward End-of-Life Planning

Abstract: Planning for end-of-life (EOL) care can result in better patient outcomes and lowered health care costs. We hypothesized that knowledge and experiences with EOL care would influence patients' EOL planning (i.e., health care decisions, hospice use). Using an observational, cross-sectional design, we recruited a community sample of 331 South Floridians aged 18 to 84 (M = 44 years, SD = 14.95) to complete a questionnaire examining knowledge and opinions on EOL issues. Regression analyses showed that prior knowled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 31 publications
1
31
0
Order By: Relevance
“…Attitude toward hospice was not a significant predictor of intentions to use hospice in the multivariate model due to positive correlations of attitudes with knowledge, subjective norms, perceived control to use hospice, and preferences for EoLC. Other studies also found similar positive correlations between hospice attitudes and knowledge (Johnson et al, 2009;Ruff et al, 2011) and hospice attitudes and greater preferences for life-sustaining therapies (Johnson et al, 2008). In contrast to our findings, other studies reported that positive hospice attitudes in the general population were significantly associated with higher intentions to use hospice (Dussen et al, 2011;Park & Lee, 2012).…”
Section: Discussionsupporting
confidence: 77%
“…Attitude toward hospice was not a significant predictor of intentions to use hospice in the multivariate model due to positive correlations of attitudes with knowledge, subjective norms, perceived control to use hospice, and preferences for EoLC. Other studies also found similar positive correlations between hospice attitudes and knowledge (Johnson et al, 2009;Ruff et al, 2011) and hospice attitudes and greater preferences for life-sustaining therapies (Johnson et al, 2008). In contrast to our findings, other studies reported that positive hospice attitudes in the general population were significantly associated with higher intentions to use hospice (Dussen et al, 2011;Park & Lee, 2012).…”
Section: Discussionsupporting
confidence: 77%
“…Prior experiences with illness and medical decision‐making may be an important determinant in ACP and its perceived relevance to individuals. Several studies have examined the relationship between illness and end‐of‐life experiences and ACP, but findings have been contradictory …”
mentioning
confidence: 99%
“…As hypothesized, when the first spouse used hospice or had no ACP, the second spouse was more likely to engage in hospice or have no ACP. Results contribute to literature showing that married couples act similarly on a range of health behaviors, and literature showing that spouses are more likely to have ACP if their partner has engaged in ACP or their partner has died . We expand on our understanding of spousal concordance related to ACP and hospice use through 2 additional findings.…”
Section: Discussionmentioning
confidence: 95%
“…Results contribute to literature showing that married couples act similarly on a range of health behaviors, [11][12][13][14] and literature showing that spouses are more likely to have ACP if their partner has engaged in ACP 9,30 or their partner has died. [31][32][33][34][35] We expand on our understanding of spousal concordance related to ACP and hospice use through 2 additional findings. First, spouses who died first had approximately 10 percentage point lower rates of hospice use and ACP engagement than second spouses.…”
Section: Discussionmentioning
confidence: 97%